2004
DOI: 10.1111/j.1464-410x.2004.04858.x
|View full text |Cite
|
Sign up to set email alerts
|

P2X2 and P2X3 receptor expression in human bladder urothelium and changes in interstitial cystitis

Abstract: OBJECTIVE To investigate whether the expression of P2X3 receptors (implicated in the pathophysiology of pain) is altered in human bladder urothelium from patients with interstitial cystitis (IC, a major symptom of which is pain), and as P2X2 receptors can be co‐expressed with P2X3 receptors, to assess their expression also. PATIENTS AND METHODS Bladder tissue samples were collected from patients undergoing cystectomy or radical prostatectomy. Patients with IC were diagnosed using the international criteria. RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 27 publications
(44 reference statements)
2
101
0
1
Order By: Relevance
“…For example, both P2X 2 and P2X 3 receptor knockout mice exhibit bladder hyporeflexia (Cockayne et al 2000(Cockayne et al , 2005 and recordings from bladder primary afferent fibers show attenuated responses to mechanical bladder stimulation (Vlaskovska et al 2001). P2X 2 and P2X 3 receptor expression is increased in the urothelium of IC patients (Tempest et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…For example, both P2X 2 and P2X 3 receptor knockout mice exhibit bladder hyporeflexia (Cockayne et al 2000(Cockayne et al , 2005 and recordings from bladder primary afferent fibers show attenuated responses to mechanical bladder stimulation (Vlaskovska et al 2001). P2X 2 and P2X 3 receptor expression is increased in the urothelium of IC patients (Tempest et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…This finding confirms previous results from localization studies in animals 17 and humans. 7,8 The data presented here demonstrate that P 2 X 2 receptors are frequently expressed in neurogenic detrusor overactivity. Moreover, we found P 2 X 2 receptor expression in idiopathic detrusor overactivity in 72% of the specimens, confirming previous findings that this receptor subtype is frequently expressed in tissues from overactive detrusors.…”
Section: Discussionmentioning
confidence: 54%
“…15 Also, in patients with interstitial cystitis, P 2 X 2 receptor expression was unchanged when compared to normal detrusor tissue, whereas P 2 X 3 receptor expression was decreased. 7 Thus, the only condition altering P 2 X 2 receptor expression was idiopathic detrusor overactivity. Comparing expression in detrusor overactivity and in bladder dysfunction caused by suprasacral spinal cord injury (SCI) may, therefore, aid in answering the question if the P 2 X 2 receptors are predominantly interacting with bladder control on neuronal or muscular level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P2X3-null mice exhibit a marked urinary bladder hyporeflexia, characterized by decreased voiding frequency and increased bladder capacity 11 . Moreover, Tempest et al 23 have reported that P2X3 subunit expression changed greatly in patients with interstitial cystitis. Thus, P2X3 signalling is very important in the regulation of bladder function.…”
Section: Discussionmentioning
confidence: 99%